Increasing Sustainability in Open Learning: Prospects of a Distributed Learning Ecosystem for Open Educational Resources - Otto, Daniel; Kerres, Michael (Frontiers in Education, 2022)
The proliferation of Open Educational Resources (OER) constitutes an essential element for establishing education as a “public good” on the internet. A core objective of OER is to broaden access to educational material and improve the overall quality of teaching and learning. In this manner, OER contributes to the sustainable (re)use and (re)distribution of (educational) resources. The goal of sustainability is also visible in the latest UNSECO recommendation concerning OER, which intends to support the 2030 Sustainable Development Agenda, namely SDG 4 (Quality education). The support of SDG 4 is combined with the call to create sustainability models for OER at national, regional and institutional levels and the planning and pilot testing of new sustainable forms of education and learning. As a result, several repositories and referatories for OER provision have been developed and tested in educational institutions worldwide. However, each of these platforms contains only a relatively limited number of resources. In our article, we argue that when considered through the lens of learning innovation and sustainable development, it would be necessary to increase the discoverability of available resources at the different locations and platforms that currently are visible to only a limited number of teachers and students. To achieve this goal, the focus needs to shift from the creation and growth of new and competing platforms to intelligent ways of linking and increasing their interconnectedness. We use the concept of “learning ecosystems” to illustrate this approach of interconnected resources. Ecosystems go beyond the spatial dimension of learning by focussing on actors’ diversity and interactions. Digital (networked) learning technology is part of an ecosystem and has itself to be understood as an actor. However, we discuss that ecosystems should be reflected with caution as they can themselves entail opening and closing mechanisms. Therefore, ecosystems that rely on mechanisms of opening their contents to other platforms can realise the full potential of open learning. We describe the implications of the concept of a distributed ecosystem by presenting case studies that show how technical solutions, including metadata standards and plugins, can link contents in repositories and referatories within ecosystems. The overarching objective is that the different repositories and referatories expand and improve the sustainable use of OER by merging into a distributed learning ecosystem.